2022
DOI: 10.1002/anie.202201588
|View full text |Cite
|
Sign up to set email alerts
|

Extending the π‐Skeleton of Multi‐Resonance TADF Materials towards High‐Efficiency Narrowband Deep‐Blue Emission

Abstract: Multi-resonance TADF (MR-TADF) emitters are promising for high-resolution OLEDs, but the concurrent optimization of excited-state dynamics and color purity remains a tough challenge. Herein, three deep-blue MR-TADF compounds (BN1-BN3) featuring gradually enlarged ring-fused structures and increased rigidity are accessed by lithiumfree borylation in high yields from the same precursor, with all the emitters possessing CIE y coordinates below 0.08. Structure-property investigations demonstrate a strategic improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(100 citation statements)
references
References 60 publications
0
100
0
Order By: Relevance
“…As a result, the TADF‐OLED using NBNP exhibited a high EQE max of 28.0% based on a narrowband green EL (λ EL = 502 nm and FWHM EL = 33 nm), together with a low efficiency roll‐off. Almost simultaneously, Yang and co‐workers reported a series of deep‐blue MR‐TADF materials, BN1 , BN2 , and BN3 [ 69 ] (Figure 4, see Section 3.3 for BN3 ), with fused π‐extended MR skeletons. Owing to its increased rigidity and π‐extension, BN2 exhibited red‐shifted emission with λ PL of 464 nm and a narrower FWHM PL of 15 nm relative to BN1 (λ PL = 454 nm and FWHM PL = 18 nm in toluene).…”
Section: Boron/oxygen (B/o) and Boron/nitrogen (B/n)‐based Mr‐tadf Ma...mentioning
confidence: 99%
“…As a result, the TADF‐OLED using NBNP exhibited a high EQE max of 28.0% based on a narrowband green EL (λ EL = 502 nm and FWHM EL = 33 nm), together with a low efficiency roll‐off. Almost simultaneously, Yang and co‐workers reported a series of deep‐blue MR‐TADF materials, BN1 , BN2 , and BN3 [ 69 ] (Figure 4, see Section 3.3 for BN3 ), with fused π‐extended MR skeletons. Owing to its increased rigidity and π‐extension, BN2 exhibited red‐shifted emission with λ PL of 464 nm and a narrower FWHM PL of 15 nm relative to BN1 (λ PL = 454 nm and FWHM PL = 18 nm in toluene).…”
Section: Boron/oxygen (B/o) and Boron/nitrogen (B/n)‐based Mr‐tadf Ma...mentioning
confidence: 99%
“…In 2022, Yang et al reported three deep blue MR‐TADF emitters ( BN1 , BN2 , and BN3 ) by extending the π ‐skeleton by increasing the number of phenyl rings from 7 to 13. [ 95 ] The designed emitters were synthesized by a one‐pot lithium‐free cyclization method. All three emitters exhibited high PLQY of over 90%, with increased k RISC from BN1 to BN3 .…”
Section: Blue/deep‐blue Mr‐tadf Emittersmentioning
confidence: 99%
“…For instance, by employing boron (B) and nitrogen (N) as electron‐deficient and electron‐rich atoms, respectively, [ 23 ] B, N‐doped PAH MR‐TADF emitters are developed to exhibit both narrowband emission and high photoluminescence quantum yield (PLQY) near unity. [ 24‐32 ] Recently, carbonyl, nitrogen (C=O, N)‐doped PAH MR‐TADF emitters were designed by inserting carbonyl and nitrogen atoms as electron‐deficient and electron‐rich atoms in PAH skeletons, [ 33‐38 ] giving narrowband emissions with external quantum efficiency (EQE) over 20%. Lately, we have developed boron, sulfur (B, S)‐doped PAH as a kind of nitrogen‐free MR‐TADF emitter by incorporating B and S atoms in PAH skeleton, where S atoms not only serve as electron donors to generate MR effect with B atoms, but also play crucial roles in enhancing SOC and promoting RISC process by heavy‐atom effect.…”
Section: Background and Originality Contentmentioning
confidence: 99%